Thermophotovoltaics Basic Principles and Critical Aspects of System Design - Bauer, Thomas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Thermophotovoltaics is the science and technology associated with the direct generation of electricity from high temperature heat. Potential applications include combined heat and power, portable and auxiliary power, radioisotope space power, industrial waste heat recovery and concentrated solar power. This book aims at serving as an introduction to the underlying theory, overview of present day components and system arrangements, and update of the latest developments in the field. The emphasis is placed on the understanding of the critical aspects of efficient thermophotovoltaic system design. The aim is to assist researchers in the field.
Introduction -- PART I: Radiators (Emitters) -- Filters -- Photovoltaic Cells -- PART II: SYSTEMS -- Heat Transfer -- Cavity Design and Optical Control -- Competing Technologies -- Projected System Performances and Potential Applications.
Keywords: Engineering; Thermodynamics; Production of electric energy or power; Renewable energy sources; Engineering; Power Electronics, Electrical Machines and Networks; Thermodynamics; Renewable and Green Energy; Engineering, general